Screening of Dogs for Possible Rabies Virus Excretion - Raju S (Department of Veterinary Epidemology & Preventive Medicine, College of Veterinary and Animal Science, 2004)
Five hundred dogs, belonging to various categories viz., healthy (vaccinated and non vaccinated), sick (vaccinated and non vaccinated) and stray dogs, were screened for the possible excretion of rabies virus in an enzootic area in Trichur, Kerala, based on the observation that nonfatal rabies occurs among dog populations in enzootic or epizootic areas. The criterion selected for the screening of dogs was detection of rabies virus antigen in corneal impression or saliva using fluorescent antibody test. None of the 500 dogs was found positive for rabies viral excretion in saliva or corneal impression. The validity of the test was periodically tested with salivary swabs from rabid dogs that were brought with clinical signs suggestive of rabies. Of twelve dogs thus examined, four were positive in saliva and two were positive in corneal impression test. One dog was positive in both corneal impression and saliva. All the twelve dogs died and rabies was diagnosed by Fluorescent antibody test. Brain samples from sixty-six suspected dogs brought to the department of pathology were subjected to fluorescent antibody test and forty-nine animals found positive for rabies. The results were confirmed positive using polymerase chain reaction. Thus in the present study no evidence of non fatal, abortive or chronic rabies could be detected among dogs in the study or control group.